Gallbladder Tuberculosis Presenting as Obstructive Jaundice. Issue 6 (25th June 2020) - Varshney, Bharti; Elhence, Poonam; Soni, Subhash; Varshney, Vaibhav Kumar; Yadav, Taruna; Saha, Souvik
ABSTRACT: Isolated gallbladder tuberculosis is a rare entity, even in endemic zones. Preoperative diagnosis is usually not possible, with most of the cases being diagnosed either as cholecystitis or malignancy. Histopathological examination of the resected specimen clinches the diagnosis. We present a middle-aged man with obstructive jaundice who was diagnosed to have gallbladder malignancy clinically and radiologically and on microscopy, and was diagnosed as gallbladder tuberculosis with the involvement of the common bile duct.